2019
DOI: 10.4103/jrms.jrms_1055_18
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as a major active component of turmeric attenuates proteinuria in patients with overt diabetic nephropathy

Abstract: Background:Diabetic nephropathy (DN) is a common cause of end-stage renal disease (ESRD). The benefits and effects of renin–angiotensin system blocker drugs are obvious in decreasing albuminuria, but there is a need to find other drugs that can decrease albuminuria. The aim of our study is to evaluate the effect of short-term administration of curcumin on overt albuminuria in patients with type 2 diabetes mellitus (T2DM).Materials and Methods:A randomized, double-blind clinical trial was performed on 46 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
1
21
0
1
Order By: Relevance
“…Further studies with a larger sample size and longer duration are recommended. 36 In the present study, we have confirmed that HG can induce the changes of EMT markers, namely decreasing the epithelial marker E-ca and increasing collagen I, and BBR pretreatment exerts the potential protective effect against HG-induced EMT in NRK-52E cells.…”
Section: Discussionsupporting
confidence: 76%
“…Further studies with a larger sample size and longer duration are recommended. 36 In the present study, we have confirmed that HG can induce the changes of EMT markers, namely decreasing the epithelial marker E-ca and increasing collagen I, and BBR pretreatment exerts the potential protective effect against HG-induced EMT in NRK-52E cells.…”
Section: Discussionsupporting
confidence: 76%
“…These two compounds strongly bind to the catalytic core of the Mpro protein with higher efficacy than lopinavir, a standard antiretroviral of the protease inhibitor class X-ray crystallographic structure [ 67 ] Bioavailable curcumin diet (protein 34.2%, fat 16.5%, starch 28%, Bio-curcumin (BCM-95; Frutarom, Londerzeel, Belgium) 0.09% diet) ( C. longa ) Eight obese cats were fed to diet for two 8-week periods (cross-over study design) while maintaining animals in an obese state. Curcumin resulted in lower plasma α1-acid glycoprotein (AGP) concentration but not changed haptoglobin levels Clinical trial [ 30 ] 500 mg curcumin capsules (total: 1,000 mg) twice daily for 12 weeks ( C. longa ) In 34 β-thalassemia patients, curcumin treatment significantly reduced serum levels of nontransferrin bound iron (NTBI), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) and not affected the transferrin saturation Randomized controlled trial [ 31 ] 1,500-mg curcumin daily for 10 weeks ( C. longa ) In 22 patients with Type 2 diabetes, curcumin treatment the mean concentration of high-sensitivity CRP besides serum concentrations of triglyceride decreased Randomized controlled trial [ 32 ] Curcuminoids (500 mg TID per oral; n = 45) for a period of 4 weeks ( C. longa ) Curcuminoids were significantly efficacious in modulating all assessed inflammatory mediators: IL-6, tumor necrosis factor-α (TNF-α), CRP, calcitonin gene related peptide (CGRP), substance P and monocyte chemotactic protein-1 (MCP-1) in 45 male subjects who were suffering from chronic sulfur mustard-induced pulmonary complications Randomized controlled trial [ 53 ] Curcumin thrice a week at a dose level of 50 mg/kg b.w were administered for 9 consecutive weeks ( C. longa ) In 8 rats curcumin treatment effectively reduced the IL-6 and CRP levels in blood serum prevented the Benzo(a)pyrene-induced lung injury Preclinical in vivo [ 33 ] 500 mg (one capsule) of curcumin with each meal (three times/day after meal) for 16 weeks ( C. longa ) During the trial (4 months) in 23 patients with T2DM, the curcumin treatment significantly reversed albuminuria Randomized controlled trial [ 34 ] 200 µg of curcumin was i.p. injected daily until day 6 ( C. longa ) In mice, curcumin signi...…”
Section: Resultsmentioning
confidence: 99%
“…), studies were found for ACE activity [ 39–43 ], reverted serum albumin levels [ 24 , 34 , 44–50 ], decreased of the plasma levels of CRP [ 21–23 , 25 , 32 , 33 , 36 , 51–55 ], transferrin saturation [ 31 , 38 , 56 ], T cells regulation [ 25–29 , 35 , 37 , 57–65 ], haptoglobin levels decreased [ 30 ], APO A-I concentrations decreased [ 20 , 66 ]. Compounds of interest reversed these activities, but in contexts unrelated to SARS-CoV-2, except for two studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularmente, la SOD reacciona con el superóxido para generar peróxido de hidrógeno, que es degradado por la CAT y el GPx. Gracias a su acción bioquímica, el SOD ayuda a suprimir la albuminuria, los niveles de TGF-β, la síntesis de colágeno y el EO en modelos experimentales 55 . En un estudio reciente, la curcumina, mayor ingrediente activo de la cúrcuma, fue capaz de reducir o atenuar la proteinuria en ND relacionado con el bloqueo de citoquinas, particularmente la TGF-β y la IL-8 56 .…”
Section: Aumento De Formación Intracelular De Ageunclassified